Improved Exercise Tolerance with Caffeine Is Associated with Modulation of both Peripheral and Central Neural Processes in Human Participants - Bowtell, Joanna L.; Mohr, Magni; Fulford, Jonathan; Jackman, Sarah R.; Ermidis, Georgios; Krustrup, Peter; Mileva, Katya N. (Frontiers in Nutrition, 2018)
Background: Caffeine has been shown to enhance exercise performance and capacity. The mechanisms remain unclear but are suggested to relate to adenosine receptor antagonism resulting in increased central motor drive, reduced perception of effort, and altered peripheral processes such as enhanced calcium handling and extracellular potassium regulation. We aimed to investigate how caffeine (i) affects knee extensor PCr kinetics and pH during repeated sets of single leg knee extensor exercise to task failure and (ii) modulates the interplay between central and peripheral neural processes. We hypothesized that caffeine-induced extension of exercise capacity during repeated sets of exercise would occur despite greater disturbance of the muscle milieu due to enhanced peripheral and corticospinal excitatory output, central motor drive and muscle contractility. Methods: Nine healthy active young men performed five sets of intense single-leg knee extensor exercise to task failure on four separate occasions: for two visits (6mg.kg-1 caffeine vs placebo), quadriceps 31P-magnetic resonance spectroscopy scans were performed to quantify phosphocreatine kinetics and pH, and for the remaining two visits (6mg.kg-1 caffeine vs placebo), femoral nerve electrical and transcranial magnetic stimulation of the quadriceps cortical motor area were applied pre- and post-exercise. Results: Total exercise time was 17.9±6.0% longer in the caffeine (1225±86s) than the placebo trial (1049±73s, p=0.02) and muscle phosphocreatine concentration (p=0.027) and pH (p=0.003) were significantly lower at task failure after caffeine ingestion. Voluntary activation (peripheral, p=0.007; but not supraspinal, p=0.074), motor evoked potential amplitude (p=0.007), and contractility (contraction time, p=0.009; and relaxation rate, p=0.003) were significantly higher after caffeine consumption, but at task failure motor evoked potential amplitude and voluntary activation were not different from placebo. Caffeine prevented the reduction in M-wave amplitude that occurred at task failure (p=0.039). Conclusion: Caffeine supplementation improved high-intensity exercise tolerance despite greater end exercise knee extensor phosphocreatine depletion and H+ accumulation. Caffeine-induced increases in central motor drive and corticospinal excitability were attenuated at task failure. This may have been induced by afferent feedback of the greater disturbance of the muscle milieu, resulting in stronger inhibitory input to the spinal and supraspinal motor neurons. However, causality needs to be established through further experiments.